Answer:
d
Step-by-step explanation:
Given y is directly proportional to x² then the equation relating them is
y = kx² ← k is the constant of proportion
To find k use the condition y =
when x =
, then
= k(
)² =
k ( multiply both sides by 8 )
1 = 2k ( divide both sides by 2 )
k = ![\frac{1}{2}](https://tex.z-dn.net/?f=%5Cfrac%7B1%7D%7B2%7D)
y =
x² ← equation of proportion
When y =
, then
=
x² ( multiply both sides by 2 )
9 = x² ( take the square root of both sides )
x = ±
= ± 3
with positive value x = 3 → d
Answer:
b. -3
Step-by-step explanation:
i hope this helps :)
Answer:
![\sqrt{1549}](https://tex.z-dn.net/?f=%5Csqrt%7B1549%7D)
Step-by-step explanation:
square 18 and square 35 then add together
Answer:
option D and E just did it hope i help
Step-by-step explanation:
Answer:
change the equation into one variable.
2 y equals 10 + x
y equals 5 + x by 2
now put that into the second equation
-3x + b parentheses 5 + x / 2 equals 11
-3x+b(5+ x/2)
-3x + b5 + bx/2 = 11